2017
DOI: 10.1007/s11191-017-9950-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationships Among Belief in Genetic Determinism, Genetics Knowledge, and Social Factors

Abstract: Genetic determinism can be described as the attribution of the formation of traits to genes, where genes are ascribed more causal power than what scientific consensus suggests. Belief in genetic determinism is an educational problem because it contradicts scientific knowledge, and is a societal problem because it has the potential to foster intolerant attitudes such as racism and prejudice against sexual orientation. In this article, we begin by investigating the very nature of belief in genetic determinism. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 109 publications
7
69
2
3
Order By: Relevance
“…Studies of monozygotic twins-a standard methodology utilized in behavior genetics-have shown for decades that twins can exhibit uncanny similarities as a direct consequence of genetic similarity. These studies also tend to engender a fascination with free will and determinism, especially as misunderstandings about the nature and meaning of heritability are thought to sometimes foster maladaptive social attitudes (Gericke et al, 2017). Intriguingly, the relationship between our intuitions about free will and knowledge about the heritability of human traits has remained largely unstudied.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of monozygotic twins-a standard methodology utilized in behavior genetics-have shown for decades that twins can exhibit uncanny similarities as a direct consequence of genetic similarity. These studies also tend to engender a fascination with free will and determinism, especially as misunderstandings about the nature and meaning of heritability are thought to sometimes foster maladaptive social attitudes (Gericke et al, 2017). Intriguingly, the relationship between our intuitions about free will and knowledge about the heritability of human traits has remained largely unstudied.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, research has been conducted to evaluate the perceptions of various groups of people on issues related to genetic influence and various aspects of human cognition (Castera & Clement, 2014;Crosswaite & Asbury, 2016;2018;Gericke et al, 2017;Human Genetics Comission, 2001;Rindermann et al, 2016a;2016b;Snyderman & Rothman, 1988;Thomas & Sarnecka, 2015;Walker & Plomin, 2005).…”
Section: Public Perceptions About Human Cognitionmentioning
confidence: 99%
“…Although recent discourses have been considering the processes of learning and school outcomes as something beyond cognitive abilities (Abed, 2016), the educational system remains to privilege such abilities through standardized assessment. Human cognitive abilities have historically been attributed more to genetic factors than to environmental factors (Gould, 1996;Snyderman & Rothman, 1988), and these, in turn, were considered immutable by various social groups (Castera & Clement, 2014;Gould, 1996;Keller, 2005;Rattan, Savani, Naidu & Dweck, 2012;Thomas & Sarnecka, 2015;Willoughby et al, 2019) The Brazilian teachers' conceptions about origin and evolution of life are more creationist than the teachers' conceptions in other Latin American countries, like Argentina and Uruguay, for example (Silva, Clément, Leão, Garros, & Carvalho, 2017). Such conception may be related to deterministic beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, "people who are especially likely to view groups as sharing a common genetic essence are more likely to espouse stereotypic beliefs about those groups" (Dar-Nimrod, Heine, 2011, p. 803). This shows that belief in genetic determinism and the forgetting of place "is a societal problem because it has the potential to foster intolerant attitudes such as racism and prejudice against sexual orientation" (Gericke et al, 2017(Gericke et al, , p. 1223). However, "knowledge about genetics and the influence of the environment on biological outcomes might reduce beliefs in genetic determinism" (Ibid, p. 1224).…”
Section: Furthermorementioning
confidence: 99%